Laminated wood and chipboard flooring towards environmentally friendly alternatives - Nieves Pimiento, Nayive; Alférez Rivas, Luis Ernesto; Morales, Néstor David; Caro Ballestas, Angie Stefani (Visión electrónica, 2014)
The article presents a series of tests conducted over a sample of chipboard and wood flooring in order to compare some physical and chemical characteristics of these materials with other alternative raw materials that may replace wood. These alternative materials comply with the quality standards established by regulations on the conservation of the environment. Thus, a comparison is made between the results of tests on samples of chipboard and wood flooring and some of the research that has been done on the characteristics of laminated bamboo to be used as raw material in laminate flooring.